RESPON FASE PERTUMBUHAN BEBERAPA GENOTIPE JAGUNG LOKAL SULAWESI TENGGARA TERHADAP KONDISI KEKURANGAN AIR - Wijayanto, Teguh; Sadimantara, Gusti Ray; Etikawati, Made (Jurnal Agroteknos, 2012)
The research was conducted to test the potency of several local maize genotypes (landraces) of Southeast Sulawesi and to find the genotypes that were tolerant to less water conditions. The research was performed in a plastic house at the experimental farm of Agriculture Faculty, University of Halu Oleo. The research was arranged in a Randomized Complete Design (RCD) with 2 treatment factors. The first factor was water availability level (A), consisted of 3 (three) levels (A0, A1 dan A2), and the second factor was maize genotype, consisted of 9 local maize and 1 national variety (Arjuna). Research results showed that the less water conditions (A1 and A2) had negative effects on maize vegetative variables (plant height, plant diameter, leaf number and length of leaf tip). On the other hand, the genotype treatment had significant effect on plant height, plant diameter, and length of leaf tip. Genotipe G7 dan G6 had the highest plant height, while G1 had the biggest plant diameter. Keywords: less water condition, local maize genotype, vegetative stage